Anteseden dan Konsekuensi Tekanan Peran (Role Stress) pada Auditor Independen - Dyah Sih Rahayu (The Indonesian Journal of Accounting Research, 2013)
This study examines antecedents to and consequences (outcomes) of role stress (role conflict and role ambiguity) experienced by independent auditors. Boundary spanning activities (BSA), perceived environmental uncertainty (PEU) and formalization are hypothesized to be antecedent to role conflict and role ambiguity, while job satisfaction, performance, job related tension and intent to leave are investigated as consequences of auditors’ role stress.The respondents are auditor independent. Data for the study were collected from 80 public accounting firms. The sampling method used is random sampling.In total 341 questionnaires were distributed, 91 were returned, for a response rate of 26,68 percent.Using Structural Equation Modeling of AMOS (Analysis of Moment Structure) Program, the result of this study indicates that BSA is a critical variable affecting  role stress auditors experience on the job. PEU and formalization are not  significant antecedent to independent auditors’ role stress. Role conflict and role ambiguity are related to several dysfunctional job outcomes. Role conflict is related to job satisfaction and job related tension, while role ambiguity is related to job performance, job satisfaction and intent to leave.